Electricity and Homosexuality: from 19th‐century American Sexual Health Literature to D. H. Lawrence. (August 2015) - Halliday, Sam
Abstract: This paper surveys a range of scientific, popular scientific and literary texts from the late‐19th‐ to the early 20th‐centuries in order to demonstrate electricity's importance within theories of sexuality, in general, and homosexuality, in particular.